Prophylactic Use of Implantable Cardioverter-Defibrillators in the Prevention of Sudden Cardiac Death in Dialysis Patients: The Prospective, Randomized, Controlled ICD2 Trial. Issue 23 (4th June 2019) - Jukema, J. Wouter; Timal, Rohit J.; Rotmans, Joris I.; Hensen, Liselotte C. R.; Buiten, Maurits S.; de Bie, Mihaly K.; Putter, Hein; Zwinderman, Aeilko H.; van Erven, Lieselot; Krol-van Straaten, M. Jacqueline; Hommes, Nienke; Gabreëls, Bas; et al.
Abstract : Background: Patients with end-stage renal disease who are undergoing dialysis are reported to be at high risk of sudden cardiac death (SCD), and to date, no therapy has been shown to be effective in reducing this risk. The feasibility and value of prophylactic implantable cardioverter-defibrillator (ICD) implantation to prevent SCD is uncertain. Methods: We conducted the ICD2 trial (Implantable Cardioverter-Defibrillator in Dialysis Patients), a prospective, randomized, controlled study investigating the value and safety of ICD implantation to prevent SCD in 200 patients on dialysis with a left ventricular ejection fraction ≥35%, after adequate screening and optimization of other treatments. The primary end point was SCD. Secondary end points were all-cause mortality and ICD-related complications. Results: The trial was stopped as per the recommendation of the data and safety monitoring board for futility reasons after inclusion of 188 patients, 97 in the ICD group and 91 in the control group. The median duration of follow-up was 6.8 years (interquartile range, 3.8–8.8 years). SCD occurred in 19 of 188 cases (10.1%), 11 of 97 in the ICD group and 8 of 91 in the control group. The cumulative SCD incidence at 5 years was 9.7% (95% CI, 3.3%–16.2%) in the ICD group and 7.9% (95% CI, 1.7–14.0%) in the control group, resulting in a hazard ratio of 1.32 (95% CI, 0.53–3.29; P =0.55). Overall, 99 of 188 patients died (52.7%), 52 in the ICD group and 47 in the control group. Five-year survival probability was 50.6% (95% CI, 39.8%–61.5%) in the ICD group and 54.5% (95% CI, 43.0–66.0%) in the control group, resulting in a hazard ratio of 1.02 (95% CI, 0.69–1.52; P =0.92). Among 80 patients who received an ICD, 25 adverse events related to ICD implantation occurred. Conclusions: In a well-screened and well-treated population undergoing dialysis, prophylactic ICD therapy did not reduce the rate of SCD or all-cause mortality, which remained high. Clinical Trial Registration: URL: http://www.controlled-trials.com . Unique identifier: ISRCTN20479861. Abstract : Supplemental Digital Content is available in the text.